2021
DOI: 10.1187/cbe.20-05-0088
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Students’ Understanding of Complex Biological Systems

Abstract: The aim of this study was to investigate how students can be supported to visualize and reason about complex biological problems from a systems thinking perspective. Four design guidelines are presented to foster students’ systems thinking in biology education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thus, the principles logically build on each other step by step. This relationship between the principles is a prerequisite for systems knowledge [ 70 ] and deep learning [ 53 ], and it helps prevent surface-learning of disconnected facts as in a learning progression [ 71 ]. Consequently, the expert view as presented in this study, seems to facilitate systems thinking, deep learning, and a possible learning progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the principles logically build on each other step by step. This relationship between the principles is a prerequisite for systems knowledge [ 70 ] and deep learning [ 53 ], and it helps prevent surface-learning of disconnected facts as in a learning progression [ 71 ]. Consequently, the expert view as presented in this study, seems to facilitate systems thinking, deep learning, and a possible learning progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies for fostering systems thinking have emerged from the literature. Our study focused on the three most prominent, as identified by Gilissen et al (2021): (1) Modeling; (2) Cross-level reasoning; and (3) Use of systems language.…”
Section: Fostering Systems Thinkingmentioning
confidence: 99%
“…Different insights can be gained from examining different levels which can lead to a better understanding of the emergent characteristics of the system as a whole (Weintrop et al, 2016). Challenging students to reason between various levels of organization has been shown to improve system thinking (Verhoeff et al, 2008;Gilissen et al, 2021).…”
Section: Modelingmentioning
confidence: 99%
“…To address the complexity and relevance of course material in the context of biological sciences, a variety of educational approaches has been used, including addressing complexity and transforming it into a tool of discovery ( 7 ), providing simulation tools ( 8 , 9 ), and using structured peer interaction ( 10 ) and collaboration ( 11 ). Creating disease-focused project-based curricula ( 6 ) and laboratory projects ( 12 ) and actively encouraging attempts to integrate material into a larger picture as a natural part of learning ( 2 ) have also been reported as ways to address complexity and emphasize the relevance of scientific material.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of implementing such approaches include the specifics of the student body (background and goals), scalability, tracking, and integration into the educational process. However, recent advances in educational tools ( 9 ) and better integration of online approaches ( 13 ) provide new opportunities for project-based approaches with improved scalability and tracking as well as organic integration of primary research literature and student-based discovery.…”
Section: Introductionmentioning
confidence: 99%